Comparative analysis of macular characteristics in mCNV and contralateral eyes - Huang, Gongyu; She, Xiangjun; Zhang, Yun; Zhang, Zongduan; Shen, Lijun (Frontiers in Medicine, 2024)
Purpose: To illustrate the characteristics of perforating scleral vessels in macular regions between mCNV eyes and contralateral eyes in unilateral mCNV patients.This was a retrospective study that included patients with unilateral or bilateral naive mCNV. The study aimed to identify and analyze the distribution of perforating scleral vessels (PSVs) in the macular region of mCNV eyes and eyes was fewer than the contralateral eyes ((1.00 (1.00-2.00) vs. 2.00 (0.75-3.00), p = 0.030). The mChT in mCNV eyes was thinner than the contralateral eyes (36.00 (25.00-53.75) µm vs. 46.00 (31.00-75.25) µm, p = 0.001). The mean grade of DCA in mCNV eyes was higher than that in contralateral eyes (3.00 (3.00-3.00) vs. 3.00 (2.00-3.00), p = 0.004). When DCA involved the macular region, there were more PSVs in contralateral eyes than in mCNV eyes (1.50 (1.00-2.00) vs.2.00 (1.00-3.00), p = 0.042). Similarly, when DCA involved the foveal region, there were more PSVs in contralateral eyes than in mCNV eyes (1.50 (1.00-2.00) vs. 3.00 (2.00-4.00), p = 0.004). The grade of DCA and mChT were valuable factors for predicting mCNV eyes (AUC = 0.6566, p = 0.021; AUC = 0.6304, p = 0.029; respectively). When the extent of DCA exceeded the foveal region, the count of PSVs was a good diagnostic factor for predicting mCNV (AUC = 0.7430, p = 0.003).The mean amount of PSVs was significantly lower in the mCNV eyes compared to the contralateral eyes. When the extent of DCA exceeded the foveal region, the count of PSVs was a good diagnostic factor for predicting mCNV.Myopic eyes with a higher grade of DCA and a thinner mChT were more likely to develop mCNV.